Environmental drivers of harvestmen assemblages (Arachnida: Opiliones) from Neotropical rainforest landscapes - Andrade, Alessandra Rodrigues Santos de; Lira, André Felipe de Araujo; Salomão, Renato Portela; Alvarado, Fredy; Souza, Adriano Medeiros de; Silva, Marcio Bernardino da; Delabie, Jacques Hubert Charles (Austral Entomology, 2022)
Understanding the effects of environmental conditions on biodiversity may provide cues regarding the resilience of ecological communities facing human activities in tropical forests. Under this scenario, harvestmen are among the most ideal models for understanding the ecological dynamics associated with shifts in environmental conditions. In this study, we evaluated how changes in attributes related to environmental conditions shape harvestmen assemblages in the Atlantic Forest. We assessed the effect of environmental transformation in four forest fragments with different proportions of native forest cover based on their environmental attributes (temperature, humidity, leaf litter depth and cover, and herbaceous vegetation cover) on harvestmen species richness, abundance, and composition. Overall, 865 harvestmen individuals belonging to six families and 41 species were sampled. The effects of environmental conditions on harvestmen assemblages were context-dependent. In the most conserved fragment, there was an increase in harvestmen richness and abundance with increasing temperature. Furthermore, herbaceous vegetation cover negatively affected harvestmen richness and abundance. Species turnover was the main driver of harvestmen beta diversity in all forest fragments. With the results presented herein, we demonstrate that harvestmen species richness and abundance are modulated by landscape modifications and subsequent alterations in the environment resulting from human-induced disturbance. Our results highlight the importance of considering environmental transformations at a large spatial scale (i.e., landscape) and local scale (i.e., environmental attributes) to design appropriate conservation strategies for Brazilian Atlantic Forest. © 2022 Australian Entomological Society.
Keywords: Arachnids; Atlantic forest; Conservação; Community ecology; Mata atlântica